Sytuacja majątkowa klasztoru cystersów w Sulejowie w XVIII i na początku XIX wieku (do kasaty w 1819 roku) .......... 13 - Kośka, Małgorzata (Dzieje i kultura Cystersów w Polsce, 2025)
THE ECONOMIC SITUATION OF THE CISTERCIAN MONASTERY IN SULEJÓW IN THE 18TH AND AT THE BEGINNING OF THE 19TH CENTURIES (UNTIL THE DISSOLUTION IN 1819)In the 18th and at the beginning of the 19th centuries the Cistercian monastery in Sulejów, one of the richest during its medieval economic boom, possessed only a small fraction of its former fortune. At last three factors had an impact on its economic situation: 1) the long lasting litigation on the borders with the nearby Premonstratensians monastery in Witów, which ended with the agreement in the year 1742; 2) the litigations with the kings’ officials – prefect (starosta) of Piotrków on the level of taxation paid by the monastery to the royal treasure; 3) the conflict with the inhabitants of two towns, which belonged to the monastery – Sulejów and Mogielnica, who complained about the fiscal pressing of the monastic administration. The second strife was resolved by the exchange of properties between the monks and voivode of Rawa – Bazyli Walicki. According to the agreement form of 1779, (confirmed by the Parliament in 1790) Mogielnica was exchanged for the villages Woźniki and Błogie, which were closer to the monastery. In 1795, after the 3rd partition of Poland, the town Sulejów was in the Prussian part and the monastery itself in the Austrian part. The Cistercians lost the properties on the left “Prussian” bank of the Pilica river, which had formed the majority of their possessions. The monastery and the town were united in one state in 1807 in the Duchy of Warsaw, and after 1815 in the Kingdom of Poland, but this time in different dioceses. The town Sulejów was in the archbishopric of Gniezno, while the monastery in the newly established bishopric of Kielce. Detailed estimation of the property of the monastery was done after its dissolution in the year 1819. According to this assessment the debt of the Cistercian monastery in Sulejów was 40 000 zloty, and the liability (some of them were not to reclaim) was 43,000 zloty. This text does not intend to describe the entire issue though it may stimulate further research into the history of the Cistercian monastery in Sulejów.